2001
DOI: 10.1002/pola.1109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and specific biodegradation of novel polyesteramides containing amino acid residues

Abstract: Novel polyesteramides were synthesized from p‐nitrophenyl esters of sebacic or adipic acids and diamines containing α‐amino acid ester groups. The optimal polymerization condition was 60 °C in N,N‐dimethylformamide. The structures of these polymers were confirmed by IR and NMR. The number‐average molecular weights of these polyesteramides ranged from 2280 to 23,600 (except for the polymers containing glycine residues), depending on the nature of the amino acid used. The biodegradability of the polyesteramides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…The resulting polymers were soluble in strong acids (formic, dichloroacetic and trifluoroacetic acid) and chlorinated polar solvents such as chloroform and dichloromethane. The synthesis of PEAs from the reaction of p-nitrophenyl esters of sebacic or adipic acids and diamines containing !-amino acid ester groups was studied by Fan et al [196] (Figure 18). The biodegradability of the resulting polymers was investigated by in vitro hydrolysis with proteases and a lipase as catalysts in borate buffer solutions.…”
Section: Poly(ester-amide)smentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting polymers were soluble in strong acids (formic, dichloroacetic and trifluoroacetic acid) and chlorinated polar solvents such as chloroform and dichloromethane. The synthesis of PEAs from the reaction of p-nitrophenyl esters of sebacic or adipic acids and diamines containing !-amino acid ester groups was studied by Fan et al [196] (Figure 18). The biodegradability of the resulting polymers was investigated by in vitro hydrolysis with proteases and a lipase as catalysts in borate buffer solutions.…”
Section: Poly(ester-amide)smentioning
confidence: 99%
“…Currently available synthetic biodegradable elastomers are primarily composed of crosslinked aliphatic PEs, which suffer from deficiencies including (1) high crosslink Figure 18. Synthesis of the optically active and biodegradable PEAs from amino acids, 2-aminoethanol, and dicarboxylic acid [196] densities, which results in exceedingly high stiffness, (2) rapid degradation upon implantation, or (3) limited chemical moieties for chemical modification. Bettinger et al [202] developed a new class of synthetic, biodegradable and chiral elastomeric PEAs, poly(1,3-diamino-2-hydroxypropane-copolyol sebacate)s, composed of crosslinked networks based on an amino alcohol ( Figure 19).…”
Section: Poly(ester-amide)smentioning
confidence: 99%
“…Other types of preformed monomers were condensed with activated esters in solution [37,[42][43][44][45][46][47][48] or with dicarboxylic acid dichlorides or activated esters by interfacial polymerisation [49][50][51][52][53][54][55][56][57]. Polymerization of diamide-diesters with diols yields alternating PEAs which have a higher degree of crystallinity than the corresponding random PEAs [58][59][60].…”
Section: Regular Peas With Aaee Sequencesmentioning
confidence: 99%
“…Several poly(ester-amide)s (PEAs) containing α-amino acids have been synthesized and the effects of the α-amino acid building blocks in PEAs main chain on biodegradability was reported [12][13][14] . PEAs based on 1,2-ethanediol, adipic acid and amino acids such as glycine, leucine, phenylalanine were synthesized and the degradation studies indicated that polymers containing glycine were not degraded with proteolytic enzymes (chymotrypsin and elastase) 15 .…”
Section: Introductionmentioning
confidence: 99%